2013
DOI: 10.1039/c3ra40469b
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid-assisted synthesis of superparamagnetic CoFe2O4 nanostructures for the selective adsorption of organic dyes

Abstract: We report a facile synthesis of superparamagnetic CoFe 2 O 4 nanostructures with the assistance of an amino acid (lysine). Monodisperse CoFe 2 O 4 nanospheres and nanoparticles were obtained by adjusting the synthesis parameters (such as the molar ratio of reactants and the solvent). The samples were characterized through scanning electron microscopy, transmission electron microscopy, X-ray diffraction, thermogravimetric analysis, and Fourier-transform infrared spectroscopy. The magnetic property and measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…There is no doubt that Pt/CoFe 2 O 4 particles with grain and grain boundary will become promising magnetic catalytic materials [4,15] properties of between superparamagnetism without magnetic hysteresis, paramagnetism or antiferromagnetism, and ferrimagnetism or ferromagnetism [17][18][19][20][21][22][23]. It turned out that this unique ferrimagnetic characterization was due to the existence of various magnetic small and large multidomains from grain and grain boundary configurations of various as-prepared CoFe 2 O 4 materials in heat treatment process used [10].…”
Section: Size and Shapementioning
confidence: 99%
See 2 more Smart Citations
“…There is no doubt that Pt/CoFe 2 O 4 particles with grain and grain boundary will become promising magnetic catalytic materials [4,15] properties of between superparamagnetism without magnetic hysteresis, paramagnetism or antiferromagnetism, and ferrimagnetism or ferromagnetism [17][18][19][20][21][22][23]. It turned out that this unique ferrimagnetic characterization was due to the existence of various magnetic small and large multidomains from grain and grain boundary configurations of various as-prepared CoFe 2 O 4 materials in heat treatment process used [10].…”
Section: Size and Shapementioning
confidence: 99%
“…In particular, Fe 2 Although various commercial Fe-, Ni-, Co-based ferrite powders were produced in decades ago, they enabled large potential of modern applications and technologies of magnetic recording media, various lithiumion batteries (LIBs) and fuel cells (FCs) for sustainable development of energy and environment [2,3,15,16,27,32,33]. In recent years, Co-, Ni-, and Fe-based ferrites with inexpensive costs have been of commercial importance, such as microwave components and defense [17][18][19][20][21][22][23]. In CoFe 2 O 4 ferrites, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnetic and catalytic abilities of ferrite make it potential to enhance the treating efficiency and also make the adsorbents recyclable [29]. Dong et al [30] found that CoFe 2 O 4 nanosphere consisting of nanoparticles display high adsorption performance on organic dyes. Ai et al [31] combined the AC with CoFe 2 O 4 to create a composite which could be used as a promising and effective adsorbent for the removal of malachite green from water.…”
Section: Introductionmentioning
confidence: 99%
“…Cobalt ferrite (CoFe 2 O 4 ) nanocrystals with spinel structure have attracted signicant attention for environmental remediation because of their outstanding properties, such as high saturation magnetization, and size-and shape-dependent magnetic behaviour. 27 Although some studies have reported the preparation and adsorption properties of CoFe 2 O 4 /graphene nanocomposites, the trivial process of preparation, 28 slow removal rate, 29 and low adsorption capacities 30,31 hinder their applications in industrial wastewater treatment, which still remains a challenging task. In addition, Chen 32 et al reported a one-step method to prepare CoFe 2 O 4 -rGO by ball-milling, and the as-prepared CoFe 2 O 4 -rGO could be used for organic dye removal by photocatalytic degradation.…”
Section: Introductionmentioning
confidence: 99%